Pathfinders for the Future? Indigenous Rights and Traditional Knowledge in Sweden - Dahlström, Åsa Nilsson; Dahlin, Johanna; Tunón, Håkan (Sustainability, 2021)
Indigenous peoples have for the past decades increasingly argued that not only is their traditional knowledge to be recognized in the management of their traditional territories, but that Indigenous control and self-governance over territories and natural resources are crucial for long-term sustainability of the land and cultural revitalisation of its people. In recent years, the Saami in Sweden have also presented themselves as pathfinders, offering advice and solutions for a more sustainable future not only for the Saami society, but for all of Sweden. This paper investigates how Saami claims for rights and stewardship in environmental management are related to Saami cultural revitalisation, within a Swedish colonial framework. It is based on an investigation of the Saami policy positions expressed in policy documents and opinion pieces produced by organisations representing the Saami, linking claims for rights and environmental stewardship with cultural revitalisation and a more sustainable development for all.